Impact of Obesity on Short-Term Outcomes in Patients Undergoing Retroperitoneal Laparoscopic/Retroperitoneoscopic Adrenalectomy for Benign or Malignant Adrenal Diseases: A Meta-Analysis - Maurizio Zizzo; Andrea Morini; Magda Zanelli; Chiara Grasselli; Francesca Sanguedolce; Sze Ling Wong; Munyaradzi G. Nyandoro; Andrea Palicelli; Giuseppe Broggi; Nektarios I. Koufopoulos; Lucia Mangone; Angelo Cormio; et al. (Medicina)
Background and Objectives: Retroperitoneal laparoscopic adrenalectomy (RLA) is one of two laparoscopic procedures used to treat benign and malignant adrenal diseases. Obesity in patients undergoing minimally invasive adrenal surgery is a frequently discussed topic. Our meta-analysis aimed to provide updated evidence by comparing intraoperative and perioperative outcomes on non-obese (NOb) and obese (Ob) patients who underwent RLA due to benign or malignant disease. Materials and Methods: We performed a systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed/MEDLINE, Scopus, Web of Science (Science and Social Science Citation Index), and Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials (CENTRAL)) databases were used to identify articles of interest. The meta-analysis was performed using RevMan [Computer program] Version 5.4. Results: The four included comparative studies (809 patients: 552 NOb versus 257 Ob) covered an approximately 15-year-study period (2007–2022). All the included studies were observational in nature. By comparing the Ob and NOb groups, shorter operative time and lower overall postoperative complication rates in the NOb population were recorded through the meta-analysis. Considering the subgroup analysis (BMI ≥ 30 kg/m2), just the operative time maintained statistical significance. Conclusions: Obesity did not appear to impact RLA safety and effectiveness. Due to important biases (small overall sample size and few analyzed events), the interpretation of our results must be a careful one. Later randomized and multi-center trials may help the confirmation of our results.